BMC Public Health - Pafitis, Natalie; Verduci, Lorena; Booker, Chris; Sun, Zhijia; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Public Health is an open access, peer-reviewed journal that considers articles on the epidemiology of disease and the understanding of all aspects of public health. The journal has a special focus on the social determinants of health, the environmental, behavioral, and occupational correlates of health and disease, and the impact of health policies, practices and interventions on the community. BMC Public Health welcomes manuscripts in the following broad areas of research: Biostatistics and methods Chronic disease epidemiology Dental public health Digital health Disaster and emergency preparedness and response Education and training in public health Environmental health Global health and human rights Health behavior and health promotion Health communication Health economics and outcomes research Health policies, systems and management Infectious disease epidemiology Injury and violence prevention Maternal and child health Mental health Nutritional health and epidemiology Occupational health Physical activity and health Public health informatics Social determinants of health As a BMC Series journal, BMC Public Health upholds the principle that editorial decisions are based on scientific validity rather than the perceived interest or impact of a study. Manuscripts must have a scientifically sound research question, employ suitable methods and analysis, and adhere to community-agreed standards within the research field. We encourage submissions from all researchers, recognizing the importance of diverse perspectives and inclusive representation in the scientific community.
Keywords: Public health; Epidemiology; Environmental health; Biometry; Pharmacology; Public Health; Epidemiology; Environmental Health; Biostatistics; Pharmacology